2021
DOI: 10.3390/antibiotics11010014
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan, Hibiscus and Propolis in the Management of Uncomplicated Lower Urinary Tract Infections: A Systematic Review and Meta-Analysis

Abstract: Background: In the era of antibiotic resistance, an antibiotic-sparing approach presents an interesting alternative treatment of uncomplicated cystitis in women. Our aim is to perform a systematic review and meta-analysis to compare the effectiveness and safety profile of a medical device containing xyloglucan, hibiscus and propolis (XHP) in women with uncomplicated cystitis. Methods: Relevant databases were searched using methods recommended by the Preferred Reporting Items for Systematic Reviews and Meta-Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In a review and meta-analysis, Cai et al found a statistically significant difference in UTI clinical or microbiological resolution between the use of the medical device and the comparator (three randomized clinical trials; 178 patients; OR: 0.13; 95% CI: 0.05–0.33; p < 0.0001). Moreover, no clinically significant adverse effects were reported in their studies [ 28 ]. In an observational prospective study by Cai et al [ 18 ], 61 women with recurrent UTIs were given the medical device for six months.…”
Section: Discussionmentioning
confidence: 99%
“…In a review and meta-analysis, Cai et al found a statistically significant difference in UTI clinical or microbiological resolution between the use of the medical device and the comparator (three randomized clinical trials; 178 patients; OR: 0.13; 95% CI: 0.05–0.33; p < 0.0001). Moreover, no clinically significant adverse effects were reported in their studies [ 28 ]. In an observational prospective study by Cai et al [ 18 ], 61 women with recurrent UTIs were given the medical device for six months.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, hibiscus and propolis might exert a beneficial effect at the urinary level, while XG might provide a protective barrier against bacteria in the intestinal tract [113]. More recently, the reported data have been re-evaluated, confirming that the product that combines XG, hibiscus and propolis has superior effectivity in adult women with uncomplicated cystitis [114].…”
Section: Mucosal Protectantmentioning
confidence: 91%
“…XHP (Xyloglucan, Hibiscus, and Propolis) XHP (xyloglucan, hibiscus, and propolis) is a medical technology product containing, in its form marketed in Greece, 100 mg of each of the three ingredients. It has been shown to have positive effects in a randomized controlled trial for the treatment of lower UTIs but as an adjuvant to antibiotic treatment [38,39].…”
Section: Arctostaphylos Uva-ursi Extractmentioning
confidence: 99%